The Evolution of the Department of Indian Affairs' Central Registry Record-Keeping Systems: 1872-1984 - Darcy, Sean (Archivaria, 2004)
This paper is a case study of record-keeping practices for textual records at the Canadian Department of Indian Affairs from 1872 to the mid-1980s. It illustrates that changes made to the department's various central registry systems reflected its organizational structure and the evolution of its functions and responsibilities. A comprehension of how records were organized, categorized, and maintained provides researchers with a powerful tool when attempting to navigate the complex records universe of the Department of Indian Affairs. RÉSUMÉ Cet article présente les pratiques de gestion des documents textuels du ministère des Affaires Indiennes entre 1872 et le milieu des années 1980. Il montre que les changements aux différents systèmes de registre central du ministère reflètent son organisation structurelle ainsi que l'évolution de ses fonctions et de ses responsabilités. La possibilité de comprendre comment les documents étaient organisés, classés et tenus à jour, permet aux chercheurs de mieux naviguer dans l'univers complexe des documents du ministère des Affaires Indiennes.